Studies on Nutritional Profile and Mineral Bioavailability of some Solanum Species Consumed as Fruits in Ekiti State, Nigeria - Oyeyemi Sunday Dele; Oyedele Alfred Adedayo; Ismaila Grace Kehinde (Turkish Journal of Agriculture: Food Science and Technology)
African eggplants are highly valued constituents of the Nigerian food. However, their nutritional potentials have not been fully tapped due to inadequate information on their nutritional and anti-nutritional qualities. This present study investigated the proximate, minerals, anti-nutrient contents as well as the estimation of mineral ratios and Mineral Safety Index of four selected edible solanum species namely, Solanum anguivi, S. gilo, S. menalogena and S. aethiopicum. The proximate contents (%) ranged from 4.19-5.46 (moisture content), 1.71-2.49 (crude fat), 4.57-5.45 (crude ash), 3.76-4.93 (crude protein), 5.20-6.30 (crude fiber) and 77.14-78.58 (carbohydrate). The solanum species were good sources of energy with total metabolizable energy of 1.458MJ-1.484MJ. The four solanum species contained high K, Ca, Mg, low Fe, Mn, Zn and Cu, while amount of Cd, Ni and Pb were very low. The mineral ratios of K/Na, Ca/Mg, Ca/K, Zn/Cu and [K/(Ca+Mg)] were below the minimum good ratios levels of 1.0, 4.17, 4.0, 8.0 and 2.2 respectively which are good for man. The anti-nutrient contents revealed low phytate, oxalate and cyanide levels. The calculated Phytate/Zn, Phytate/Ca and Oxalate/Ca were lower than the threshold levels and would support absorption and bioavailability of Zn and Ca in the samples while that of Phytate/Fe was above the critical value and this indicates unavailability of iron in these eggplant fruits. The mineral differences observed showed that S. menalogena and S. aethiopicum had greater minerals while the Mineral Safety Index results revealed that the body could not be overloaded with any of the minerals investigated. The eggplants are rich in fiber, ash, carbohydrate and minerals with moderate protein. The low level of the anti-nutrient is good and poses no deleterious effect when consumed. The eggplants have nutritional health benefits; hence, their consumption should be encouraged to address food insecurity in Nigeria